PENDAMPINGAN KELUARGA DALAM KEBERHASILAN PEMBERIAN ASI EKSKLUSIF DI DESA KALIUKAN WILAYAH KERJA PUSKESMAS ASTAMBUL - Dewi, Vonny Khresna Dewi; Rusmilawaty; Tunggal, Tri (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2025)
ABSTRACT Kaliukan Village is located in Astambul District, Banjar Regency, with 34 6-month-old babies, based on May 2024 data. Of the 6-month-old babies in Kaliukan Village who faced problems with exclusive breastfeeding, 33 were not exclusively breastfed, representing 97% of the total. The solution used is to provide counseling on the importance of providing exclusive breastfeeding, correct breastfeeding techniques and methods, breast care methods, Oxytocin Massage, how to express breast milk and how to store breast milk properly, especially with limited knowledge and inadequate practices and lack of support from husbands/families. by providing education and assistance related to providing exclusive breastfeeding, so as to increase the understanding and awareness of mothers, husbands/families and cadres about the importance of providing exclusive breastfeeding for optimal health and growth of babies. The method we will implement includes mentoring 20 parents and 5 cadres, through education and mentoring on Exclusive Breastfeeding including providing Exclusive Breastfeeding, correct breastfeeding techniques and methods, breast care methods, Oxytocin Massage, how to express breast milk and how to store breast milk properly by involving cadres. The contribution of target partners and target groups is responsible for facilitating the location of community service activities and maintaining the sustainability of the implementation of community activities for parents. The target of this community service is to increase the number of cadres and parents regarding exclusive breastfeeding, improve infant health and growth (BB/TB), and improve good nutrition in infants. Mandatory output targets are publication in online electronic media on the Poltekkes Banjarmasin YouTube, videos, leaflets and increased empowerment of partners. The implementation of community service activities and evaluations revealed that mothers understood and were able to practice them, and that breast milk flowed smoothly. This success was also due to the good collaboration between midwives and Posyandu cadres, as well as the support of husbands and families.